2012
DOI: 10.4137/cpath.s8798
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of KRAS Mutation Assessment in Tumor DNA and Circulating Free DNA in Plasma and Serum Samples

Abstract: Testing for mutations in the KRAS oncogene for patients with metastatic colorectal cancer (mCRC) is generally performed using DNA from formalin-fixed paraffin-embedded tumor tissue; however, access to specimens can be limited and analysis challenging. This study assessed the identification of KRAS mutations in circulating free DNA (cfDNA) using a commercially available KRAS polymerase chain reaction (PCR) kit. Matched plasma, serum and tumor samples were available from 71 patients with mCRC who had received pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 24 publications
6
24
0
1
Order By: Relevance
“…The codon 12 mutation of KRAS is the most common mutation pattern, and was used to detect KRAS mutation in tumor tissue and plasma DNA (37,38). Previous studies demonstrated that plasma KRAS detection was not only convenient but also highly sensitive in detection of KRAS mutation as compared with tumor tissue assessment (39,40). In the present study, we found that the incidence of KRAS mutation was significantly higher in cancer patients than in healthy controls.…”
Section: Discussionsupporting
confidence: 61%
“…The codon 12 mutation of KRAS is the most common mutation pattern, and was used to detect KRAS mutation in tumor tissue and plasma DNA (37,38). Previous studies demonstrated that plasma KRAS detection was not only convenient but also highly sensitive in detection of KRAS mutation as compared with tumor tissue assessment (39,40). In the present study, we found that the incidence of KRAS mutation was significantly higher in cancer patients than in healthy controls.…”
Section: Discussionsupporting
confidence: 61%
“…Published studies on cfDNA in cancer patients give remarkably little detail about the impact of different extraction methods on DNA alterations analysis, such as KRAS mutation. Although the high specificity (97%) of KRAS detection has been documented, very low (25%) sensitivity was achieved [22]. Our study provides confirmation that the QIAamp DNA Blood Mini kit gives the lowest cfDNA yield, as is consistently recorded by others [12,14,15,23].…”
Section: Discussionsupporting
confidence: 88%
“…The figures were produced by STATA and modified by Microsoft Ò Paint (version 6.1, Redmond, WA). [20] de Kok et al [43] Iinuma et al [44] Ryan et al [31] Yen et al [12] Liu et al Miyano et al [21] Spindler et al [38] Taly et al [19] Gutierrez et al …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, blood is a potential substitute for tumor tissue that provides a non-invasive, easily accessible, and repeatedly available source of biological material that can be used in mutation analysis and to monitor molecular changes during cancer therapy. Several studies have provided data on K-ras mutations detected in plasma DNA [18,19] and serum DNA [12,20,21], but researchers have not reached a consensus on the effectiveness of conducting blood testing as an alternative to tissue biopsy to detect K-ras mutation [11,22,23].…”
mentioning
confidence: 99%